PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN PRODUK, TERHADAP KEPUASAN KONSUMEN ESSPECTO COFFE DI JL. FLAMBOYAN KOTA MANADO - Aprillia Christiany Soetanto; Silvya L. Mandey; Djurwati Soepeno (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effect of service quality, facilities, and products on customer satisfaction at Esspecto Coffee, Flamboyan Street, Manado. This research employed a quantitative descriptive method with a survey approach. The population consisted of all Esspecto Coffee customers, and a sample of 100 respondents was selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression, along with validity, reliability, t-test, and F-test analyses. The results reveal that service quality, facilities, and products have a positive and significant influence, both partially and simultaneously, on customer satisfaction. These findings confirm that the better the quality of service, the more adequate the facilities, and the more consistent the product quality, the higher the level of customer satisfaction. The practical implication of this study is thatEsspecto Coffee management should continuously improve these three aspects to strengthen customer loyalty and maintain competitive advantage amid the growing coffee shop industry in Manado.